An Evaluation of the Indonesian Ministry of Religious Affairs' Policies Concerning Terrorism, Radical Religious Movements in Curriculum Content and Pedagogy of Secondary Education - Nurlena Rifai (Universitas Islam Negeri (UIN), 2016)
Abstract The purpose of this study is to evaluate the Indonesian government policies on curriculum and pedagogy that responds the global phenomenon of radical and violent forms of Islam. Specifically I investigate whether the Ministry of Religious Affairs has designed a curriculum content in Islamic Religious Studies for secondary education that discusses key concepts such as radicalism, jihadi-takfiri movements, religious violence, and intolerance towards other faiths. These issues are a central concern to Muslims in Indonesia. This research uses a qualitative approach and descriptive method. My research attempts to answer why the Ministry of Religious Affairs has not included curriculum content that deals with contemporary issues of violent Islamic movements. The data had been collected through observation, documentation and  interviews a number of officials of the Ministry of Religious Affairs and Ministry of National Education, education experts and practitioners, and students. The result of my study will be a recommendation to the Ministry of Religious Affairs and Ministry of Culture and Primary and Secondary Education for developing curriculum content deals with the question of radicalism and religious violence in a direct and honest way. Abstrak Penelitian ini bertujuan untuk mengevaluasi kebijakan pemerintah Indonesia pada kurikulum dan pedagogik yang merespon fenomena global dari radikalisme dan bentuk kekerasan dalam Islam. Khususnya, saya menyelidiki apakah Kementerian Agama telah merancang konten kurikulum pada mata pelajaran Agama Islam untuk sekolah menengah yang mendiskusikan konsep-konsep seperti radikalisme, gerakan jihadi-takfiri, kekerasan beragama, dan intoleransi terhadap keyakinan lain. Isu-isu tersebut merupakan perhatian utama bagi muslim di Indonesia. Metode penelitian ini menggunakan pendekatan deksriptif kualitatif. Penelitian saya berusaha menjawab mengapa Kementerian Agama tidak memasukkan konten kurikulum yang menyelesaikan isu-isu kontemporer tentang gerakan islam radikal. Data diambil melalui observasi, dokumentasi, dan wawancara sejumlah pejabat kementerian agama dan kementerian pendidikan, para ahli pendidikan, praktisi dan siswa. Hasil penelitian ini berupa rekomendasi kepada kementerian agama dan kementerian pendidikan dan kebudayaan pendidikan dasar dan menengah untuk mengembangkan konten kurikulum yang mengatasi pertanyaan tentang radikalisme dan kekerasan beragama dengan cara yang langsung dan jujur. How to Cite : Rifai, N (2015). An Evaluation of  the Indonesian Ministry of Religious Affairs' Policies Concerning Terrorism, Radical Religious Movements in Curriculum Content and Pedagogy of Secondary Education. TARBIYA: Journal Of Education In Muslim Society, 2(2), 178-189. doi:10.15408/tjems.v2i2. 3181. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i2.3181